A pediatric echocardiographic Z-score nomogram for a developing country: Indian pediatric echocardiography study - The Z-score - Rajendra Kumar Gokhroo; Avinash Anantharaj; Devendra Bisht; Kamal Kishor; Nishad Plakkal; Rajeswari Aghoram; Nivedita Mondal; Shashi K Pandey; Ramsagar Roy (Wolters Kluwer Medknow Publications, 2017)
Background: Almost all presently available pediatric echocardiography Z-score nomograms are based on Western data. They may not be a suitable reference standard for assessing the sizes of cardiac structures of children from developing countries. Objective: This study's objective was to collect normative data of 21 commonly measured cardiovascular structures using M-mode and two-dimensional echocardiography in Indian children aged between 4 and 15 years and to derive Z-score nomograms for each. Subjects and Methods: The study was conducted at two centers in India . Ajmer, Rajasthan, and Mohali, Punjab. We studied a community-based sample involving healthy school going children. After excluding children with cardiovascular abnormalities on the screening echocardiogram, 746 children were included in the final analysis. Echocardiographic assessment was performed using a Philips iE33 system. Results and Analysis: For each parameter measured, seven models were evaluated to assess the relationship of that parameter with the body surface area and the one with the best fit was used to plot the Z-score chart for that parameter. Z score charts were thus derived. Conclusions: The Z-score nomograms derived by this study may be better alternatives to the Western nomograms for use in India and other developing countries for preprocedural decision making in the pediatric population. However, they will require validation in large-scale studies before they can become clinically applicable.